Quantifying the Ancillary Benefits of the Representative Concentration Pathways on Air Quality in Europe - Milan Šcasný; Emanuele Massetti; Jan Melichar; Samuel Carrara (Fondazione Eni Enrico Mattei (FEEM), 2015)
This paper presents estimates of the economic benefit of air quality improvements in Europe that occur as a side effect of GHG emission reductions. We consider three climate policy scenarios that reach radiative forcing levels in 2100 of three Representative Concentration Pathways (RCPs). These targets are achieved by introducing a global uniform tax on all GHG emissions in the Integrated Assessment Model WITCH, assuming both full as well as limited technological flexibility. The resulting consumption patterns of fossil fuels are used to estimate the physical impacts and the economic benefits of pollution reductions on human health and on key assets by implementing the most advanced version of the ExternE methodology with its Impact Pathway Analysis. We find that the mitigation scenario compatible with +2°C reduces total pollution costs in Europe by 76%. Discounted ancillary benefits are more than exteuro2.5 trillion between 2015 and 2100. The monetary value of reduced pollution is equal to exteuro22 per abated ton of CO2 in Europe. Less strict climate policy scenarios generate overall smaller, but still considerable, local benefits (14 exteuro or 18 exteuro per abated ton of CO2). Without discounting, the ancillary benefits are in a range of exteuro36 to exteuro50 per ton of CO2 abated. Cumulative ancillary benefits exceed the cumulative additional cost of electricity generation in Europe. Each European country alone would be better off if the mitigation policy was implemented, although the local benefits in absolute terms vary significantly across the countries. We can identify the relative losers and winners of ancillary benefits in Europe. In particular, we find that large European countries contribute to as much as they benefit from ancillary benefits. The scenarios with limited technology flexibility do deliver results that are similar to the full technology flexibility scenario.
Keywords: Q47; Q51; Q53; Q54; 330; Ancillary benefits; External costs; Climate change mitigation; Integrated Assessment Models; ExternE; Impact Pathway Analysis